Work participation and mental and physical health outcomes among a national community-dwelling sample of older adult men and women in India - Pengpid S. (2023)
This study aimed to assess the association between work participation and various health outcomes in older community-dwelling adults in India. The cross-sectional sample consisted of 14,342 male and 8342 female participants (≥60 years) from the Longitudinal Aging Study in India (LASI) Wave 1 in 2017–2018. Among older men (≥60 years) who had ever been working, 45.5% and among older women (≥60 years), 35.7% were working. In adjusted Poisson, linear or logistic regression analyses, work participation was among both men and women associated with better self-rated health status, lower prevalence of insomnia symptoms, lower prevalence of heart disease or stroke, lower prevalence of diabetes, lower functional limitations, lower physical inactivity, and higher heavy episodic drinking. In addition, among men, work participation was associated with current tobacco use, and among women, work participation was associated with higher cognitive functioning, and lower prevalence of depressive symptoms.